Assessing the “virality” of a road safety communication campaign intended to change behavior: a case study in Spain - Faus, Mireia; Alonso, Francisco; Fernández, Cesáreo; Useche, Sergio A. (Frontiers in Sustainable Cities, 2024)
The relationships between above-the-line (ATL) and below-the-line (BTL) communication and advertising strategies have been studied in many fields and procedures. Likewise, the interrelationships between both communicative typologies, when they exist, either strategically induced or spontaneously, are also known concerning their reinforcing effects. However, in the social communication field, specifically road safety communication, these interrelationships have been little studied, and few case studies have been done, particularly of those that have stood out as particularly significant. Thus, this paper investigates the implementation process of an ATL awareness campaign of the Spanish Traffic Authority (DGT -General Directorate of Traffic) through the analysis of key digital reach indicators. Despite the foreseeable limitations of this research regarding the repercussions and positive impact on society of the DGT communication campaign, it is nevertheless a contribution of interest regarding the digital impact that has been generated in networks (BTL communication) from a DGT campaign broadcast on various media such as television, radio, posters, and social networks. Thus, from a methodology based on an exact delimitation (two DGT TV spots -from 2022-generating a quantitative activity on X (formally Twitter) that had never before produced DGT spots), significant conclusions and results have been reached related to issues of age groups, loyalty and distortion of messages, communication impact strategies, among others.